Capacity Retention for (De)lithiation of Silver Containing α-MnO2: Impact of Structural Distortion and Transition Metal Dissolution. Issue 11 (1st January 2018) - Huang, Jianping; Housel, Lisa M.; Quilty, Calvin D.; Brady, Alexander B.; Smith, Paul F.; Abraham, Alyson; Dunkin, Mikaela R.; Lutz, Diana M.; Zhang, Bingjie; Takeuchi, Esther S.; Marschilok, Amy C.; Takeuchi, Kenneth J.
Abstract : Crystallite size reduction is a strategy utilized to increase deliverable capacity by decreasing the path length for lithium ion diffusion. However, reduction in crystallite size may also exacerbate unfavorable reactions within a battery limiting cycle life. Here, differences in capacity retention are observed for silver containing α-MnO2 (silver hollandite, AgHol), with two crystallite sizes. Under 30 mA/g discharge, the smaller crystallite size material (AgHol-S, 5 nm) delivers 266 mAh/g initial capacity with 91% capacity decrease from cycles 2–50. In contrast, the larger crystallite size material (AgHol-L, 14 nm) has an initial capacity of 129 mAh/g and only 9% decrease from cycles 2–50. A second electrochemical test was conducted using a capacity limit rather than a voltage limit. Under those test conditions, the structural distortion for the two materials observed by X-ray absorption spectroscopy (XAS) was similar, yet the terminal voltage decrease was more significant for the small crystallite sized sample. Determination of Mn dissolution revealed Mn solubility 5.4X higher for AgHol-S than AgHol-L with accompanying higher Mn deposition on the negative electrode and increased cell impedance. This study provides quantitative determination of capacity fade as related to structural distortion and transition metal dissolution as related to crystallite size.